2020
DOI: 10.1002/pmrj.12427
|View full text |Cite
|
Sign up to set email alerts
|

Acute Fifth Metatarsal Tuberosity Fractures: A Systematic Review of Nonoperative Treatment

Abstract: Objective: Acute metatarsal fractures are a common lower extremity injury. Although surgery may be recommended in specific cases, most are treated nonoperatively. Treatment protocols vary significantly among practitioners, with no consensus on the most efficacious approach. This systematic review aims to identify the effect of treatment protocols on union rate and functional outcome after an acute fifth metatarsal tuberosity fracture. Literature Survey: Multiple databases, including CINAHL, EMBASE, MEDLINE, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Historically, surgery was recommended for a displacement greater than 2 mm, or comminution in Zone 1 fractures and various operative interventions have been described (76,77,78,79,80,81). A prospective study showed no benefit of immobilization vs symptomatic treatment for avulsion fractures of the base of the fifth metatarsal (48), while a recent systematic review opted for non-operative treatment, regardless of technique (82). Involvement of more than one-third of the cubometatarsal joint may require open reduction and screw fixation using tension band wiring or a small fragment screw (2.0-2.7 mm) (40,83,84); however, the latter is found to be superior (83).…”
Section: Zone 1 -Non-displaced and Displaced Tuberosity Avulsion Fracturesmentioning
confidence: 99%
“…Historically, surgery was recommended for a displacement greater than 2 mm, or comminution in Zone 1 fractures and various operative interventions have been described (76,77,78,79,80,81). A prospective study showed no benefit of immobilization vs symptomatic treatment for avulsion fractures of the base of the fifth metatarsal (48), while a recent systematic review opted for non-operative treatment, regardless of technique (82). Involvement of more than one-third of the cubometatarsal joint may require open reduction and screw fixation using tension band wiring or a small fragment screw (2.0-2.7 mm) (40,83,84); however, the latter is found to be superior (83).…”
Section: Zone 1 -Non-displaced and Displaced Tuberosity Avulsion Fracturesmentioning
confidence: 99%
“…10,13,14,22,35,36 In accordance with other authors' findings, our results support a nonoperative treatment approach for nondisplaced zone 1 fractures. 1,3,5,8,10,18 Previous studies have indicated better results for WBAT strategy regarding pain, function, and time to fracture union compared with NWB. 7,14,29,36 Our findings show no differences between these strategies, supporting WBAT to be the treatment of choice for these fractures.…”
Section: Zone 1 Fracturesmentioning
confidence: 99%
“…3,19 Nonoperative treatment of nondisplaced zone 1 fractures yields good outcomes with both symptomatic treatment and cast immobilization, whereas displaced zone 1 fractures could benefit from operative treatment. 1,3,4,8,10,18 Zone 2 and zone 3 fractures usually are nondisplaced, and both operative and nonoperative treatment have been advocated. Several studies argue for operative fixation to be the treatment of choice in young and athletic patients because of anticipated higher union rates and a shorter time to union.…”
Section: Introductionmentioning
confidence: 99%
“…Avulsion fractures of the tuberosity have good healing potential, and nonoperative treatment is generally recommended 53 . This is particularly true for extra-articular and nondisplaced fractures 2,12,51,85-97 . In the nonathletic population, excellent results with union rates of 100% have been reported for displaced fractures and fractures involving the articular facet to the cuboid 13,52,94,98-100 .…”
Section: Principles Of Treatmentmentioning
confidence: 99%